Resistance to recombinant human erythropoietin therapy in haemodialysis patients - Elísio Costa; Margarida Lima; Susana Rocha; Petronila Rocha-Pereira; Flávio Reis; Elisabeth Castro; Frederico Teixeira; Vasco Miranda; Maria do Sameiro Faria; Alfredo Loureiro; Alexandre Quintanilha; Luís Belo; et al. (Cadernos de Saúde)
To better clarify the mechanism of resistance to recombinant human erythropoietin (rhEPO) therapy in haemodialysis patients, we studied systemic changes associated with this resistence in haemodialysis patients under rhEPO therapies, with particular interest on inflammation, leukocyte activation, ironstatus, oxidative stress and erythrocyte damage. We studied 63 chronic kidney disease (CKD) patients under haemodialysis and rhEPO therapies (32 responders and 31 non-responders to rhEPO therapy) and 26 healthy volunteers. In 20 of the CKD patients (10 responders and 10 non-responders to rhEPO therapy), blood samples were also collected immediately after dialysis to study the effect of the haemodialysis procedure. When compared to controls, haemodialysis patients presented lymphopenia, which results, at least in part, from a decrease in total circulating CD3+ T-lymphocytes and affect both the CD4+ and the CD8+ T-cell subsets. These lymphocytes presented markers of enhanced continuous activation state and enhanced ability to produce Th1 related cytokines. Furthermore, haemodialysis patients presented raised markers of an inflammatory process, and of an enhanced neutrophil activation, as showed by the high serum levels of elastase. Concerning to iron status, patients showed increased ferritin and prohepcidin serum levels, and a decrease in transferrin. Furthermore, some changes were observed in erythrocyte membrane protein composition and in band 3 profile, being the decrease in spectrin the most significant change. Higher plasma levels of total antioxidant status (TAS), lipidic peroxidation (TBA) and TBA/TAS ratio were also found. When comparing the two groups of patients, we found that non-responders presented a significant decrease in total lymphocyte and CD4+ T-cell counts, a more accentuated inflammatory process and indicators of enhanced neutrophil activation. No significant differences were found in serum iron status markers between the two groups of patients, except for the soluble transferrin receptor, which was higher among non-responders. Prohepcidin serum levels were significantly lower in non-responders, but were higher than those in the control group. An accentuated decrease in erythrocyte membrane spectrin, alterations in band 3 profile [decrease in band 3 proteolytic fragments (Pfrag) and in Pfrag/band 3 monomer ratio], and a trend to higher values of membrane bound haemoglobin were also found in non-responders patients. In conclusion, although the etiology of resistance to rhEPO therapy is still unknown, our work confirms that inflammation seems to have an important role in its pathophysiology. We also showed that resistance to rhEPO therapy is associated with “functional” iron deficiency, lymphopenia and CD4+ lymphopenia, higher elastase plasma levels, increased interleukin-7 serum levels, and alterations in erythrocyte membrane protein structure and in band 3 profile. Further studies are needed tounderstand the rise in inflammation with the associated need inhigher doses of rhEPO and the reduced iron availability.